2014
DOI: 10.1371/journal.pone.0101784
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Genetic Contributions to Error Processing: A Multimodal Neuroimaging Study

Abstract: BackgroundNeuroimaging studies reliably identify two markers of error commission: the error-related negativity (ERN), an event-related potential, and functional MRI activation of the dorsal anterior cingulate cortex (dACC). While theorized to reflect the same neural process, recent evidence suggests that the ERN arises from the posterior cingulate cortex not the dACC. Here, we tested the hypothesis that these two error markers also have different genetic mediation.MethodsWe measured both error markers in a sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 72 publications
3
14
1
1
Order By: Relevance
“…To our knowledge, this is one of the first studies to examine the functional correlates of this gene in human SUD – and the first to use functional neuroimaging for this purpose. This research augments work aiming to clarify the mechanisms underlying opioid genes’ modulation of addictive disorders in humans [25, 26, 93] and of error-related processing more generally [94]. More importantly, our results suggest an intermediate phenotype that can increase understanding of the PENK gene’s contribution to disease-relevant phenotypes such as SUD [41].…”
Section: Discussionsupporting
confidence: 65%
“…To our knowledge, this is one of the first studies to examine the functional correlates of this gene in human SUD – and the first to use functional neuroimaging for this purpose. This research augments work aiming to clarify the mechanisms underlying opioid genes’ modulation of addictive disorders in humans [25, 26, 93] and of error-related processing more generally [94]. More importantly, our results suggest an intermediate phenotype that can increase understanding of the PENK gene’s contribution to disease-relevant phenotypes such as SUD [41].…”
Section: Discussionsupporting
confidence: 65%
“…As reviewed by Manoach and Agam [], several genes from the dopaminergic system have been associated with ERN or the related deltaERN measure (difference between the ERN and CRN), with an association of the DAT1 VNTR and conflicting evidence across studies for association of DRD2 , DRD4 , and COMT . The DRD4 variant rs1800955 (T allele) was associated with increased ERN in one study included in the review [Kramer et al, ], but a more recent study reported an opposite direction of effect [Agam et al, ]. An additional study of the COMT Val158Met polymorphism supported the association of the Val allele with increased ERN, an effect that was moderated by the acute administration of dopamine [Mueller et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…To date, there has only been one replicated finding. Two studies have reported associations between ERN amplitude and a polymorphism of the DRD4 receptor gene (Agam et al, 2014; Kramer et al, 2007). However, whereas this SNP accounted for approximately 13% of the variance in ERN amplitude in the initial study of Kramer et al, it only accounted for about 3% of variance in the subsequent study of Agam and colleagues (the “winner's curse”; Ioannidis, 2008), and this latter effect was statistically significant only because a one-tailed test was used.…”
Section: 0 Recommendations To Advance Endophenotype Geneticsmentioning
confidence: 99%